Detection of the jaundice-related G71R mutation in the UGT1A1 gene by denaturing high performance liquid chromatography (DHPLC) - Retno Sutomo; Sunartini Hapsara; Suryono Yudha Patria; Hajime Nakamura (Paediatrica Indonesiana, 2009)
Background  The  G71R mutation in the UGT1A1 gene has  beenassociated with neonatal jaundice  and  other  cases  of  hereditary,unconjugated hyperbilirubinemia in several Asian populations.Currently,  DNA  sequencing  is  the  only  method  available  toidentify the mutation, which can be time- and  labor-intensive,particularly for such projects  as  population-based genetic studies.A relatively new method, denaturing high performance liquidchromatography (DHPLC),  is  increasingly used to  detect  variousmutations.Objective  The  aim  of  the present study was to investigate theability of DHPLC to  detect  the G71R mutation, in comparisonwith the gold standard of sequencing analysis.Methods Seventy-two infants were enrolled. Following genomicDNA  extraction, exon 1 of the UGT1A1 gene was amplified  bypolymerase chain reaction (PCR). Afterwards, the G71R mutationwas simultaneously,  and  blindly, determined in all subjects  byDHPLC and sequence analysis.  The  performance  of  the DHPLCanalysis, compared  to  the sequence analysis, was assessed in termsof  sensitivity  and  specificity.Results DHPLC detected the G71 R mutation in  31  individuals.Of  these,  26  were heterozygous and 5 were homozygous for themutation. This method did not find the mutation in  41  otherindividuals. Sequence analysis produced identical results for allindividuals.Conclusion DHPLC analysis  is  capable  of  detecting the G71Rmutation  in  the  UGT1A1  with  a degree  of  sensitivity  andspecificity  (100%  each)  that  is  comparable to sequencing analysis.